Inhibition of the intracellular domain of Notch1 results in vascular endothelial cell dysfunction in sepsis - Liu, Tingyan; Zhang, Caiyan; Ying, Jiayun; Wang, Yaodong; Yan, Gangfeng; Zhou, Yufeng; Lu, Guoping (Frontiers in Immunology, 2023)
Background Notch signaling is critical for regulating the function of vascular endothelial cells (ECs). However, the effect of the intracellular domain of Notch1 (NICD) on EC injury in sepsis remains unclear. Methods We established a cell model of vascular endothelial dysfunction and induced sepsis in a mouse model via lipopolysaccharide (LPS) injection and cecal ligation and puncture (CLP). Endothelial barrier function and expression of endothelial-related proteins were determined using CCK-8, permeability, flow cytometry, immunoblot, and immunoprecipitation assays. The effect of NICD inhibition or activation on endothelial barrier function was evaluated in vitro. Melatonin was used for NICD activation in sepsis mice. The survival rate, Evans blue dye of organs, vessel relaxation assay, immunohistochemistry, ELISA, immunoblot were used to explore the specific role of melatonin for sepsis induced vascular dysfunction in vivo. Results We found that LPS, interleukin 6, and serum collected from septic children could inhibit the expression of NICD and its downstream regulator Hes1, which impaired endothelial barrier function and led to EC apoptosis through the AKT pathway. Mechanistically, LPS decreased the stability of NICD by inhibiting the expression of a deubiquitylating enzyme, ubiquitin-specific proteases 8 (USP8). Melatonin, however, upregulated USP8 expression, thus maintaining the stability of NICD and Notch signaling, which ultimately reduced EC injury in our sepsis model and elevated the survival rate of septic mice. Conclusions We found a previously uncharacterized role of Notch1 in mediating vascular permeability during sepsis, and we showed that inhibition of NICD resulted in vascular EC dysfunction in sepsis, which was reversed by melatonin. Thus, the Notch1 signaling pathway is a potential target for the treatment of sepsis.